THE INFLUENCING FACTORS AFFECTING CONSUMERS BUYING DECISION TOWARDS "MADE IN MALAYSIA" PRODUCT: A PROPOSED MODEL - Weillin Tan Wei Loon; Shaizatulaqma Kamalul Ariffin; Nabsiah Abdul Wahid (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The purpose of this study is to review the relationship between product, price, place, promotion (4Ps), brand knowledge and consumers’ buying decision toward "Made in Malaysia" product and to propose a model to identify the influencing factors on this behaviour. The model is based on a review of past studies on consumers’ buying decision, product, price, place, promotion, brand knowledge and Theory of Marketing Mix. The model can be used to understand consumers’ buying decision toward "Made in Malaysia" product. The significance of this study lies in the fact that it will provide vital insights on how product, price, place, promotion and brand knowledge affect consumers’ buying decision toward "Made in Malaysia" product.